2016
DOI: 10.1038/npp.2016.172
|View full text |Cite
|
Sign up to set email alerts
|

Altered Glutamate and Regional Cerebral Blood Flow Levels in Schizophrenia: A 1H-MRS and pCASL study

Abstract: The neurobiology of schizophrenia (SZ) may be altered in older versus younger adults with SZ, as less frequent episodes of symptom exacerbation and increased sensitivity to medications are observed in older age. The goal of this study was to examine the effect of age and diagnosis on glutamate and cerebral blood flow (rCBF) in adults with SZ and healthy controls. Young and older adults with SZ and healthy controls were recruited to participate in this study. Participants completed a neuropsychological battery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 56 publications
(72 reference statements)
6
25
1
Order By: Relevance
“…If a single study was reported as 2 samples, the largest sample was included. In case of partial overlap, both studies were included with weighting based only on the non-overlapping sample for the smaller study ( 28 , 29 ). We also excluded studies where no information was available on voxel placement ( 30 ) or when study-specific Cramer-Rao Lower Bound (a measure of MRS signal quality and reliability) was exceeded for myo-inositol signal ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…If a single study was reported as 2 samples, the largest sample was included. In case of partial overlap, both studies were included with weighting based only on the non-overlapping sample for the smaller study ( 28 , 29 ). We also excluded studies where no information was available on voxel placement ( 30 ) or when study-specific Cramer-Rao Lower Bound (a measure of MRS signal quality and reliability) was exceeded for myo-inositol signal ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…Proportion of gray matter in the spectroscopic voxel did not significantly differ between patients and controls (t = 1.49, p = .14). MR spectroscopy data for 37 patients and 28 controls were included in previous reports [38,39] but none of the stress-induced KYNA data were previously reported.…”
Section: Mrsmentioning
confidence: 99%
“…; Wijtenburg et al . ). Moreover, meta‐analyses suggested a decline with age and disease duration in the levels of glutamate and glutamine (Schwerk et al .…”
mentioning
confidence: 97%
“…Bustillo et al (2017) reported recently that, with age, N-acetylaspartate increases in cortical grey matter and decreases in white matter of schizophrenia patients (Bustillo et al 2016). Alterations have also been abundantly reported for glutamine and glutamate concentrations: increased glutamine, glutamate and/or and the ratio of glutamine-to-glutamate (Gln/Glu) have been found in early stages of the disease (Tibbo et al 2004;Hashimoto et al 2005;Bustillo et al 2009Bustillo et al , 2017de la Fuente-Sandoval et al 2011;Brandt et al 2016;Merritt et al 2016), whereas decreased levels of these amino acids have often been observed in chronic patients (Tayoshi et al 2009;Ohrmann et al, 2005;Chiappelli et al 2015;Brandt et al 2016;Wijtenburg et al 2017). Moreover, meta-analyses suggested a decline with age and disease duration in the levels of glutamate and glutamine (Schwerk et al 2014), as well as N-acetylaspartate (Brugger et al 2011).…”
mentioning
confidence: 99%